Effective aggregation of various summarization techniques. Issue 2 (March 2018) - Mehta, Parth; Majumder, Prasenjit
Abstract: A large number of extractive summarization techniques have been developed in the past decade, but very few enquiries have been made as to how these differ from each other or what are the factors that actually affect these systems. Such meaningful comparison if available can be used to create a robust ensemble of these approaches, which has the possibility to consistently outperform each individual summarization system. In this work we examine the roles of three principle components of an extractive summarization technique: sentence ranking algorithm, sentence similarity metric and text representation scheme. We show that using a combination of several different sentence similarity measures, rather than only one, significantly improves performance of the resultant meta-system. Even simple ensemble techniques, when used in an informed manner, prove to be very effective in improving the overall performance and consistency of summarization systems. A statistically significant improvement of about 5% to 10% in ROUGE-1 recall was achieved by aggregating various sentence similarity measures. As opposed to this aggregation of several ranking algorithms did not show a significant improvement in ROUGE score, but even in this case the resultant meta-systems were more robust than candidate systems. The results suggest that new extractive summarization techniques should particularly focus on defining a better sentence similarity metric and use multiple sentence similarity scores and ranking algorithms in favour of a particular combination.